Many-year Dynamics and Current Trends of the Pavlovsk Reservoir Area Water Chemical Composition Changes - Airat R. Hafizov; Salavat А. Valitov; Liliya A. Kamaletdinova; Razilya А. Nizamova; Ilgiz Z. Gaisin (Водное хозяйство России: проблемы, технологии, управление)
At present, changes have occurred in the basin and water area of the Pavlovsky reservoir, affecting the chemical composition of the reservoir water. The combination of many factors (series of low-water years, termination of milk alloy, increase of recreational load, change of the share of diffuse contamination, etc.) do not allow to predict the modern trend of transformation of chemical composition of water. Considering that no gydro/chemical studies of Pavlovsky reservoir have been carried out in recent decades, studies of modern processes of transformation of chemical composition of this reservoir are relevant. For this purpose BashNIIVKh in 2018-2019 carried out hydro/chemical studies of the reservoir, in two years water samples were taken from the surface and from the bottom, as well as bottom deposits. In 2018 samples were taken according to 30 chemical indicators on 10 struts, and in 2019 – according to 10 chemical indicators on 7 struts. Also, the results of previous studies have been analyzed. Due to the large volume of the obtained material, this work only considered the results of studies of multi-year dynamics and modern trend of change of chemical composition of water (concentration of chemicals) in the water area of the Pavlovsky reservoir for 10 chemical indicators of water on 7 branches. Concentrations of Sr, Mn, petroleum products are shown to decrease along the length of the reservoir in the water; Increasing - Zn, Hg, phenols of organic substances; evenly distributed – Fetotal, Ptotal, Cu. In the many-year dynamics, Fetotal, Mn, petroleum products, phenols (in the inlet), COD show a trend of decrease of chemical indicators in water; Upward trend – Ptotal, Cu, Zn, phenols (in the exit). It has been established that the average annual concentrations of chemical indicators in the water of the Pavlovsky reservoir are related to the average annual inflow. The chemical values of Fe and Mn have a direct link (when the inflow increases, the concentration of the chemical index increases), and Ptotal, Cu, Zn, phenols and COD have a feedback (when the inflow increases, the concentration of the chemical index decreases).